In the Beginning of the Relationship Portugal - Lithuania: Martin Lopes and Damiano de Gois. Two Portuguese of XVI century in Lithuania - de Almeida Araujo e Esteves, Julieta Maria Aires (Lietuvos istorijos studijos, 2009)
-